The dorsal visual stream revisited: Stable circuits or dynamic pathways?. (January 2018) - Galletti, Claudio; Fattori, Patrizia
Abstract: In both macaque and human brain, information regarding visual motion flows from the extrastriate area V6 along two different paths: a dorsolateral one towards areas MT/V5, MST, V3A, and a dorsomedial one towards the visuomotor areas of the superior parietal lobule (V6A, MIP, VIP). The dorsolateral visual stream is involved in many aspects of visual motion analysis, including the recognition of object motion and self motion. The dorsomedial stream uses visual motion information to continuously monitor the spatial location of objects while we are looking and/or moving around, to allow skilled reaching for and grasping of the objects in structured, dynamically changing environments. Grasping activity is present in two areas of the dorsal stream, AIP and V6A. Area AIP is more involved than V6A in object recognition, V6A in encoding vision for action. We suggest that V6A is involved in the fast control of prehension and plays a critical role in biomechanically selecting appropriate postures during reach to grasp behaviors. In everyday life, numerous functional networks, often involving the same cortical areas, are continuously in action in the dorsal visual stream, with each network dynamically activated or inhibited according to the context. The dorsolateral and dorsomedial streams represent only two examples of these networks. Many others streams have been described in the literature, but it is worthwhile noting that the same cortical area, and even the same neurons within an area, are not specific for just one functional property, being part of networks that encode multiple functional aspects. Our proposal is to conceive the cortical streams not as fixed series of interconnected cortical areas in which each area belongs univocally to one stream and is strictly involved in only one function, but as interconnected neuronal networks, often involving the same neurons, that are involved in a number of functional processes and whose activation changes dynamically according to the context.